Reactor: effects of different pressure and temperature analysis using ANSYS / Nurul Ain Ghazali, Ts Dr Noor Iswadi Ismail and Ir Mohd Azahar Mohd Ariff - Ghazali, Nurul Ain; Ismail, Noor Iswadi; Mohd Ariff, Mohd Azahar (2021)
There are collective of incident regarding reactor safety that cause fatality either towards humans, environment and towards facilities. This incident has open the world eyes to prioritize safety especially in processing industry involving reactor. Thus, this study will focus on the fixed bed reactor reliability of the effect of pressure and temperature through analysis using ANSYS software in methanol synthesis process.